Creación de sistema móvil para la publicación de ventas y compras de repuestos de motocicleta (2023)
In the city of Bogotá D.C., Colombia, the motorcycle market is growing day by day for different reasons, among them the disorderly growth of the city, which produces job locations far from the workers' places of residence and therefore, difficulties to access the public transportation system, wasteful traffic, among others.